The Postpartum Mother's Level Of Independence Meet Your Self-Care Needs - Astutik, Puji; Erni Dwi Sabarini (Master of Public Health Program Universitas STRADA Indonesia, 2024)
Postpartum care is a follow-up action for women after giving birth. Self-care during the postpartum (postpartum) period is necessary because during the postpartum period a woman will experience many changes in herself, both physically and psychologically. Independence in self-care during the postpartum period is very important for health recovery. The aim of this research was to determine the level of independence of postpartum mothers in meeting their self-care needs in the Delima Room at RSD Kertosono. This research used a descriptive design which was carried out from 23 to 30 May 2023 in the Delima Room at RSD Kertosono. The population in this study was postpartum mothers for an average of 5 months (January to May 2023) totaling 91 respondents, the sample size was 30 postpartum mother respondents using an incidental sampling technique, the research variable was the level of independence of postpartum mothers in meeting their self-care needs. Data collection uses a questionnaire. Based on the research results, the research results of 30 respondents can be seen. The majority, namely 17 respondents (57%) have the category of independence, dependency, almost half, namely 9 respondents (30%) have the category of independence requiring help and a small portion, namely 4 respondents (13%) has the independence of the independent category to fulfill postpartum self-care needs. The results of the study stated that the majority, namely 17 respondents (57%), had the independence category to fulfill their self-care needs. This is influenced by the mother's type of birth SC (Section Caesarea), the 1st day of postpartum, the mother's education, the housewife's job and the mother having never received any information. Therefore, nurses provide encouragement and motivation so that mothers are more independent in meeting their postnatal self-care needs.